Summary of IFAS Turf and Landscape Irrigation Recommendations - Michael D. Dukes (EDIS)
AE436, an illustrated fact sheet by Michael D. Dukes, reviews current turfgrass and landscape irrigation recommendations and unifies them to provide a coordinated science-based turf and landscape irrigation recommendation. Includes comprehensive reference lists. Published by the UF Department of Agricultural and Biological Engineering. Originally published December 2008. This update April 2020.